Transformation of women's leadership through producing natural-dyed hand-woven fabrics (ethnographic study on Palue weavers) - Hendrikus Pedro; Koentjoro; Sito Meiyanto; Budi Andayani (Elsevier, 2021)
Objective: The purpose of this study was to find an explanation for the transformation process of the Palue female weavers' leadership, which changes along with changes in the use of color materials in the sarong from chemical colors that are harmful to health and not in accordance with tradition to natural color materials that are safer and in accordance with tradition. Methods: An ethnographic approach was used in this study. Data collection was carried out for 17 months through direct involvement in the activities of producing natural-dyed and hand-woven traditional fabrics done by 15 families. Result: The results showed that a transformation of leadership took place in each of these families. Conclusion: Replacing chemicals with natural ingredients that are safer in sarong coloring, not only makes women healthier but also makes them a leader in the home industry as well as becoming more empowered and daring to pass on their sarong-making skills to the next generation because natural color materials are safe for children. Women are the managers of the home industry of making naturally dyed hand-woven fabrics, involving their husbands and children. There has been a cultural change in which husbands have been willing to help their wives with the dyeing and weaving works. Leadership by women in this home industry has an impact on the decision-making process in the family, cooperatives and community.